Tintinalli's emergency medicine a comprehensive study guide - Tintinalli, Judith E.; Stapczynski, J. Stephan (McGraw-Hill, 2011)
With 418 contributors representing over 120 medical centers from around the world, this book comprehensively covers the entire field of emergency medicine -- from prehospital care, disaster preparedness, and basic resuscitative techniques -- to all the major diseases and disorders encountered in the emergency department. Unquestionably the leading text in the field, this is a true must-have reference for everyone in emergency medicine from residents to practicing physicians. The Seventh Edition is highlighted by a new full-color presentation, a companion DVD with 17 additional chapters, a greater international focus, and innovative new features and content.